No Reliable Association Between Recreational Noise Exposure and Threshold Sensitivity, Distortion Product Otoacoustic Emission Amplitude, or Word-in-Noise Performance in a College Student Population. Issue 6 (November 2018) - Le Prell, Colleen G.; Siburt, Hannah W.; Lobarinas, Edward; Griffiths, Scott K.; Spankovich, Christopher
Abstract : Objectives: The purpose of this study was to evaluate the relationship between recreational sound exposure and potentially undiagnosed or subclinical hearing loss by assessing sound exposure history, threshold sensitivity, distortion product otoacoustic emission (DPOAE) amplitudes, and performance on the words-in-noise (WIN) test. Design: Survey data were collected from 74 adult participants (14 male and 60 female), 18 to 27 years of age, recruited via advertisements posted throughout the University of Florida campus. Of these participants, 70 completed both the survey and the additional functional test battery, and their preferred listening level was measured in a laboratory setting. Results: There were statistically significant relationships between hearing thresholds and DPOAE amplitude. In contrast, performance on the WIN was not reliably related to threshold sensitivity within this cohort with largely normal hearing. The two most common exposures included bars or dance clubs, followed by music player use. There were no statistically significant relationships between individual or composite measures of recreational sound exposure, including preferred listening level, years of music player use, number of reported sound exposures, previous impulse noise exposure, or previous noise-induced change in hearing, and functional measures including threshold, DPOAE amplitude, and WIN measures. Some subjects were highly consistent in listening level preferences, while others were more variable from song to song. Conclusions: No reliable relationships between common recreational sound exposure or previous noise-induced changes in hearing were found during analysis of threshold sensitivity, DPOAE amplitude, or WIN performance in this cohort. However, the study sample was predominantly female and Caucasian, which limits generalizability of the results.